Synthesis of Modified Polycarboxylate and Its Application in Ultra-High Performance Concrete - Shuncheng Xiang (Frontiers in Materials, 2021)
Modified polyurethane prepolymer was prepared using the segmental synthesis method. Then, pectiniform polycarboxylate was synthesized at normal temperature in the complex initiation system of H2O2, APS, sodium bisulfite, Vc, and Rongalit according to the free radical polymerization reaction mechanism, using TPEG, AA, and PEG as raw materials and TGA as the chain transfer agent. Compared with commercial Sika polycarboxylate, its flowability, strength, drying shrinkage, and auto-shrinkage were studied. The experimental results show that the synthesized polycarboxylate could be better dispersed. Adding silica fume can enhance the compressive strength of ultra-high performance concrete (UHPC), while slag may decline its strength. By incorporating slag and silica fume, the drying shrinkage of UHPC was reduced, but its auto-shrinkage was increased.